2007
DOI: 10.1002/jcu.20244
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolymphoma of the liver: Sonographic findings and review of the literature

Abstract: We report a case of hepatic pseudolymphoma in a 67-year-old woman that was detected during an abdominal sonography screening. The lesion was further evaluated using CT, MRI, angiography, and contrast-enhanced sonography. The imaging features of this tumor are discussed herein. The diagnosis of pseudolymphoma was achieved via sonographically guided biopsy. The lesion regressed completely within 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…All cases reported in English are reviewed in Table 2. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The total number of cases was 26, including 5 patients in the current study. Five patients (19%) had multiple (two or three) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All cases reported in English are reviewed in Table 2. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The total number of cases was 26, including 5 patients in the current study. Five patients (19%) had multiple (two or three) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al [45] 23 Maehara et al [46] 72 F 2 1.3, 1.0 RLH 24 Willenbrock et al [47] 36 F 1 1.8 NLL Ovarian cyst, focal nodular hyperplasia of the liver 25 Sato et al [4] 75 F 1 1.4 RLH Gastric cancer, colon cancers, metastatic liver tumor 27 Ota et al [20] 63 F 1 1.6 PL Gastric ulcer, Helicobacter pylori infection 28 Machida et al [48] 53 F 3 1.5, 1.2, 1.0 RLH Autoimmune thyroiditis 29 Matsumoto et al [49] such as Sjögren's disease were reported [13] , which is similar to the liver. In other organs, several factors are thought to be associated with pseudolymphoma, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Most of the lesions reported are single in number, although multiple lesions have been also reported. [1][2][3][4][5] Usually there are just two or three lesions, however, with a large number of lesions as in our case never having been reported to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4][5] Imaging fi ndings of PL, although only a few case reports are available, are thought to refl ect these pathological features but are considered nonspecifi c. On CT, a hypodense mass on unenhanced images that is slight enhanced on early-phase images after contrast injection and subsequent washout have been reported. [1][2][3][4][5] On angiography, neovascularity and tumor stain have been documented. 4 On MR imaging, low signal intensity on T1-weighted images and slightly high signal intensity on T2-weighted images have been reported.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation